EFEKTIVITAS PERMAINAN TRADISIONAL ENGKLEK TERHADAP KEMAMPUAN MOTORIK KASAR ANAK DI SDN 14 TELAGA BIRU - Rahmawaty Parman; Rahmiyati Rizkiah Ismail; Sitti Sulistia Larasati Husain; Sri Rahayu Suratinoyo; Sri Wulan J Saleh; Sitti Lutfia Biu (Elsia: Jurnal Psikologi Manusia, 2024)
Every parent wants their child's growth and development to be optimized since the child begins to occupy the elementary school bench elementary school. When the child has been born into the world, parents have already start preparing everything in order to get the best education for the child. Education that is able to pay attention to the growth and development of students according to the level of child development aspects. Especially children's gross motor skills. Therefore, researchers try to try to provide cranklek game treatment to stimulate children's gross motor skills. Children's gross motor abilities are built from toddler age and will improve well as they get older into adulthood. several ways can optimize the gross motor abilities of early childhood, namely: through play activities. Engklek game is a traditional game that can train and stimulate children's motor skills and children can learn to coordinate all limbs gradually in an agile and agile manner. body gradually in an agile and agile manner. This research was conducted at SDN 14 Telaga Biru. This study uses quantitative methods in the form of experiments. the sample amounted to 26 subjects. The research instrument used was an observation sheet. The data analysis used was descriptive data test, normality test, and paired samples test. the results showed Asymp.Sig 0.000 <0.005. This means that the Engklek Traditional Game has an effect on the Motor Skills of the gauze